2021
DOI: 10.3389/fped.2021.648587
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Critically Ill Children Is Not all Acute: Lessons Over the Last 5 Years

Abstract: Acute kidney injury (AKI) in the pediatric intensive care unit (PICU) is an important risk factor for increased morbidity and mortality during hospitalization. Over the past decade, accumulated data on children and young people indicates that acute episodes of kidney dysfunction can have lasting consequences on multiple organ systems and health outcomes. To date, there are no guidelines for follow-up of surviving children that may be at risk of long-term sequelae following AKI in the PICU. This narrative revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Univariable analyses suggested that more severe AKI (stage 2 or worse) was even more strongly associated with 11-year outcomes, suggesting a "dose-response" effect. These ndings are consistent with previous studies with shorter follow-up [17,19,[41][42][43][44][45] . However, our ndings also suggest that the impact of AKI may somewhat wane over time; Robinson et al also found that the impact of AKI on incident CKD and HTN diagnoses lessened with time [19].…”
Section: Discussionsupporting
confidence: 93%
“…Univariable analyses suggested that more severe AKI (stage 2 or worse) was even more strongly associated with 11-year outcomes, suggesting a "dose-response" effect. These ndings are consistent with previous studies with shorter follow-up [17,19,[41][42][43][44][45] . However, our ndings also suggest that the impact of AKI may somewhat wane over time; Robinson et al also found that the impact of AKI on incident CKD and HTN diagnoses lessened with time [19].…”
Section: Discussionsupporting
confidence: 93%
“…Complications are common, including consequences of invasive catheters, mechanical ventilation, injury to the recurrent laryngeal and phrenic nerves, infection, necrotizing enterocolitis, unplanned procedures, and many more (see Table 1 ). In addition to these short-term consequences, these complications can also contribute to long-term challenges such as ventricular dysfunction, E19 , E20 , E21 , E22 atrioventricular valve regurgitation, E23 , E24 , E25 vascular access limitations, neurodevelopmental challenges, E26 , E27 , E28 chronic kidney disease, E29 , E30 , E31 , E32 , E33 hypertension, E34 proteinuria, E34 gastrointestinal complications, E8 , E35 , E36 , E37 and abnormal lung function. E20 , E38 , E39 Considering the high mortality and morbidity subsequent to surgical intervention for HLHS, the need for a fundamental change in the management of these patients should be considered, utilizing the components of all 3 currently used approaches, with a specific emphasis on minimizing morbidity as well as improving short-term survival.…”
Section: Current Results Of Intervention For Hlhs and Variantsmentioning
confidence: 99%
“…The link between pediatric AKI and the development of chronic kidney disease (CKD) has been well established in pediatric patients [8,10,45–49,50 ▪▪ ]. A recent study found that children with kidney failure had a loss of substantial numbers of potential life years, which was most notable in those who had kidney failure at younger ages [51 ▪ ].…”
Section: The Long-term Risk Of Pediatric Aki: Renal and Systemic Sequ...mentioning
confidence: 99%